2006
DOI: 10.1007/s00421-006-0225-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of muscle hardness in tetanic contractions induced by electrical stimulation in rats

Abstract: The purpose of this study was to investigate the in vivo relation between muscle hardness during an electrically induced contracting state and neuromuscular functions (M-wave and developed tension). Sixteen Sprague-Dawley rats were deeply anesthetized with urethane. Muscle hardness was measured quantitatively at the mid-portion of the gastrocnemius (GS) muscle during tetanic contractions induced by electrical stimulation (50 Hz, 100 micros duration) of the sciatic nerve or of the muscle directly. The M-wave wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Evidence from studies that did not use ultrasound elastography (e.g., using push-in meter) suggests that the increase in muscle stiffness for contractions with up to moderate intensity is mainly due to the number of cross-bridges 6,33,34) . However, push-in meters have indicated that the increase in muscle hardness is blunted at contractions with higher intensity 35) . As muscle fibers fuse at contractions of higher intensity, muscle force is increased by an increase in firing rate 36) .…”
Section: The Relationship Between Individual Muscle Stiffness (Shear mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from studies that did not use ultrasound elastography (e.g., using push-in meter) suggests that the increase in muscle stiffness for contractions with up to moderate intensity is mainly due to the number of cross-bridges 6,33,34) . However, push-in meters have indicated that the increase in muscle hardness is blunted at contractions with higher intensity 35) . As muscle fibers fuse at contractions of higher intensity, muscle force is increased by an increase in firing rate 36) .…”
Section: The Relationship Between Individual Muscle Stiffness (Shear mentioning
confidence: 99%
“…As muscle fibers fuse at contractions of higher intensity, muscle force is increased by an increase in firing rate 36) . Morisada et al 35) concluded, since muscle hardness during tetanic nerve stimulation was closely correlated with the M-wave amplitude, that the contractile activity (interactions of cytoskeletal filaments accompanied by neuromuscular transmission) and muscle membrane excitability represent mechanisms likely related to the development of muscle hardness. Therefore, currently, the conclusions based on SWE-derived data contrast the long-held hypothesis regarding motor-unit recruitment strategies.…”
Section: The Relationship Between Individual Muscle Stiffness (Shear mentioning
confidence: 99%
“…It is also not clear whether the change in muscle hardness is linear with muscle tension, i.e., muscle stiVness. Several studies have focused on the relationship between muscle hardness and muscle activation for convenient muscle force estimation using transverse measurements (e.g., Leonard et al 2003Leonard et al , 2004Gennisson et al 2005;Morisada et al 2006). In brief, these studies showed that muscle hardness is signiWcantly correlated with muscle tensile force.…”
Section: Introductionmentioning
confidence: 98%
“…Resting muscles become stiffer under several conditions, including those involving cramps and damage (Fischer, 1987 ; Murayama et al, 2000 ). Similarly, muscle fatigue has been considered as one of possible causes for the increment of muscle stiffness (Morisada et al, 2006 ; Descarreaux et al, 2010 ). It is known that a resting tension develops when muscles fail to fully relax during fatigue (Gong et al, 2000 , 2003 ).…”
Section: Introductionmentioning
confidence: 99%